Effects of exhaustive aerobic exercise on tryptophan-kynurenine metabolism in trained athletes - Strasser, B.; Geiger, D.; Schauer, M.; Gatterer, H.; Burtscher, M.; Fuchs, D. (PLOS ONE, 2016)
Exhaustive exercise can cause a transient depression of immune function. Data indicate significant effects of immune activation cascades on the biochemistry of monoamines and amino acids such as tryptophan. Tryptophan can be metabolized through different pathways, a major route being the kynurenine pathway, which is often systemically up-regulated when the immune response is activated. The present study was undertaken to examine the effect of exhaustive aerobic exercise on biomarkers of immune activation and tryptophan metabolism in trained athletes. After a standardized breakfast 2 h prior to exercise, 33 trained athletes (17 women, 16 men) performed an incremental cycle ergometer exercise test at 60 rpm until exhaustion. After a 20 min rest phase, the participants performed a 20 min maximal time-trial on a cycle ergometer (RBM Cyclus 2, Germany). During the test, cyclists were strongly encouraged to choose a maximal pedalling rate that could be maintained for the respective test duration. Serum concentrations of amino acids tryptophan, kynurenine, phenylalanine, and tyrosine were determined by HPLC and immune system biomarker neopterin by ELISA at rest and immediately post exercise. Intense exercise was associated with a strong increase in neopterin concentrations (p<0.001), indicating increased immune activation following intense exercise. Exhaustive exercise significantly reduced tryptophan concentrations by 12% (p<0.001) and increased kynurenine levels by 6% (p = 0.022). Also phenylalanine to tyrosine ratios were lower after exercise as compared with baseline (p<0.001). The kynurenine to tryptophan ratio correlated with neopterin (r = 0.560, p<0.01). Thus, increased tryptophan catabolism by indoleamine 2,3-dioxygenase appears likely. Peak oxygen uptake correlated with baseline tryptophan and kynurenine concentrations (r = 0.562 and r = 0.511, respectively, both p<0.01). Findings demonstrate that exhaustive aerobic exercise is associated with increased immune activation and alterations in monoamine metabolism in trained athletes which may play a role in the regulation of mood and cognitive processes.